Population pharmacokinetics and dosing optimization of cefathiamidine in children with hematologic infection - Zhi LJ; Wang L; Chen XK; Zhai XY; Wen L; Dong L; Jacqz-Aigrain E; Shi ZR; Zhao W (Dove Medical Press, 2018)
Li-Juan Zhi,1,2,* Li Wang,2,3,* Xing-Kai Chen,4 Xiao-Ying Zhai,3 Li Wen,3 Lei Dong,1,2 Evelyne Jacqz-Aigrain,5,6 Zhong-Ren Shi,2,* Wei Zhao1,2,4,* 1Department of Pharmacy, Children’s Hospital of Hebei Province, Shijiazhuang, People’s Republic of China; 2Pediatric Research Institute, Children’s Hospital of Hebei Province, Shijiazhuang, People’s Republic of China; 3Department of Pediatric Hematology-Oncology, Children’s Hospital of Hebei Province, Shijiazhuang, People’s Republic of China; 4Department of Clinical Pharmacy, School of Pharmaceutical Sciences, Shandong University, Jinan, People’s Republic of China; 5Department of Pediatric Pharmacology and Pharmacogenetics, Hôpital Robert Debré, APHP, Paris, France; 6Clinical Investigation Center CIC1426, INSERM, Paris, France *These authors contributed equally to this work Purpose: Cefathiamidine, a first-generation cephalosporin, has approval from the China Food and Drug Administration for the treatment of infections caused by susceptible bacteria in both adults and children. As pharmacokinetic data are limited in the pediatric population, we aimed to evaluate the population pharmacokinetics of cefathiamidine in children and to define the appropriate dose in order to optimize cefathiamidine treatment.Methods: Blood samples were collected from children treated with cefathiamidine, and concentrations were quantified by high-performance liquid chromatography and tandem mass spectrometry. Population pharmacokinetic analysis was conducted using NONMEM software.Results: Fifty-four children (age range: 2.0–11.8 years) were included. Sparse pharmacokinetic samples (n=120) were available for analysis. A two-compartment model with first-order elimination showed the best fit with the data. A covariate analysis identified that bodyweight had a significant impact on cefathiamidine pharmacokinetics. Monte Carlo simulation demonstrated that the currently used dosing regimen of 100 mg/kg/day q12h was associated with a high risk of underdosing in pediatric patients. To reach the target 70% fT>MIC, a dose of 100 mg/kg/day cefathiamidine q6h is required for effective treatment against Haemophilus influenzae.Conclusion: A population pharmacokinetics model of cefathiamidine in children with hematologic disease was established. A dosing regimen of 100 mg/kg/day cefathiamidine q6h should be used in clinical practice against H. influenza infections. Keywords: cefathiamidine, pharmacokinetics, dosing, children